2021
DOI: 10.18240/ijo.2021.06.02
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Avellino corneal dystrophy in a Chinese family after LASIK

Abstract: AIM: To reveal the importance of TGFBI gene screening for candidates with a family history of corneal disease or granular opacities in corneal stroma before refractive surgery. METHODS: A 37-year-old male (proband) underwent bilateral laser-assisted in situ keratomileusis (LASIK) in 2002, with right vision decreased significantly in 2006. The proband and other 32 members of the family underwent a detailed ophthalmic examination, including vision acuity, intraocular pressure, slit-lamp photograph, fundus examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
4
3
0
Order By: Relevance
“…However, the deposits observed in our patients exhibited distinct patterns and were located exclusively in the Bowman layer, in contrast to those in previous reports, in which the deposits were mainly located at the interface. 7,9,13 The deposits observed at the Bowman layer in Reis-Bucklers or Thiel-Behnke dystrophies bear resemblance to the OCT images shown in our study. However, distinct patterns were discerned in the slit-lamp images of our subjects.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, the deposits observed in our patients exhibited distinct patterns and were located exclusively in the Bowman layer, in contrast to those in previous reports, in which the deposits were mainly located at the interface. 7,9,13 The deposits observed at the Bowman layer in Reis-Bucklers or Thiel-Behnke dystrophies bear resemblance to the OCT images shown in our study. However, distinct patterns were discerned in the slit-lamp images of our subjects.…”
Section: Discussionsupporting
confidence: 80%
“…The precise etiology underlying the selective deposition of these deposits in the Bowman layer remains incompletely understood, although some researchers suggest that differences in the proteoglycan content or the unique ultrastructural properties of the Bowman layer may play a role. 14 Although the exacerbation of corneal dystrophy after refractive surgery is mostly observed in GCD2 cases associated with TGFBI gene mutations as reported in previous studies, 7,9,[15][16][17] only one of our patients (case 3) exhibited a missense mutation on TGFBI: c.1949C.T (p. Ala650Val), which has never been linked to GCD2. One of our patients (case 2) presented with a missense mutation in SLC4A11, which is expressed in the corneal endothelium and is correlated with congenital hereditary endothelial dystrophy.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A string analysis also showed that both TGFBI and LTBP2 (associated with congenital glaucoma) co-express, along with a possible interaction with MYOC and CYP1B1. There is also a report of glaucoma observed in a patient with TGFBI , R124H mutation, though the phenotypic details of this patient are not known (20). We also found 2 patients of ours with early onset open angle glaucoma with TGFBI mutations in a separate cohort.…”
Section: Discussionsupporting
confidence: 51%
“…A string analysis also showed that TGFBI and LTBP2 (associated with congenital glaucoma) co-express, possibly interacting with MYOC and CYP1B1 . There is also a report of glaucoma observed in a patient withTGFBI, R124H mutation, though the phenotypic details of this patient are not known (Jiang & Zhang 2021).These observations suggest an important role of TGFBI in glaucoma pathogenesis, in conjunction with other genes.…”
Section: Discussionmentioning
confidence: 80%